Monte Carlo implementation of new algorithms for the evaluation of averaged-dose and -track linear energy transfers in 62 MeV clinical proton beams. (30th November 2020) - Petringa, G; Pandola, L; Agosteo, S; Catalano, R; Colautti, P; Conte, V; Cuttone, G; Fan, K; Mei, Z; Rosenfeld, A; Selva, A; Cirrone, GAP
Abstract: We exploited the power of the Geant4 Monte Carlo toolkit to study and validate new approaches for the averaged linear energy transfer (LET) calculation in 62 MeV clinical proton beams. The definitions of the averaged LET dose and LET track were extended, so as to fully account for the contribution of secondary particles generated by target fragmentation, thereby leading to a more general formulation of the LET total. Moreover, in the proposed new strategies for the LET calculation, we minimised the dependencies in respect to the transport parameters adopted during the Monte Carlo simulations (such as the production cut of secondary particles, voxel size and the maximum steplength). The new proposed approach was compared against microdosimetric experimental spectra of clinical proton beams, acquired at the Italian eye proton therapy facility of the Laboratori Nazionali del Sud, Istituto Nazionale di Fisica Nucleare (INFN-LNS, Catania, I) from two different detectors: a mini-tissue equivalent proportional chamber (TEPC), developed at the Legnaro National Laboratories of the National Institute for Nuclear Physics (LNL-INFN) and a silicon-on-insulator (SOI) microdosimeter with 3D sensitive volumes developed by the Centre for Medical Radiation Physics of Wollongong University (CMRP-UoW). A significant increase of the LET in the entrance region of the spread out Bragg peak (SOBP) was observed, when the contribution of the generated secondary particles was included in the calculation. This was consistent with the experimental results obtained.